Metastatic Immune-Related Genes for Affecting Prognosis and Immune Response in Renal Clear Cell Carcinoma - Sun, Si; Mao, Weipu; Wan, Lilin; Pan, Kehao; Deng, Liting; Zhang, Lei; Zhang, Guangyuan; Chen, Ming (Frontiers in Molecular Biosciences, 2022)
Background: Renal clear cell carcinoma, as a common cancer of the urinary system, 25~30% patients are metastatic at initial diagnosis, and 20~30% patients have a tendency of recurrence and metastasis after local surgery. With the rapid development of tumor immunology, immune agents have brought new directions to tumor therapy. However, no relevant studies have explored the role of immune-related genes in kidney cancer metastasis. Methods: Co-expressed metastatic immuno-related differential expression genes (mIR-DEGs) were screened by GSE12606, GSE43752 and immunorelated genes. Then, differential expression analysis, prognostic analysis, univariate and multivariate Cox regression analysis in KIRC were performed to determine independent prognostic factors associated, and the risk prognostic model was established. The correlation of hub mIR-DEG with clinicopathological factors, immune invasion and immune checkpoints was analyzed, and the expression of hub mIR-DEG and their effect on tumor were re-evaluated by OCLR scores in KIRC. Results: By comprehensive bioassay, we found that FGF17, PRKCG, SSTR1 and SCTR were mIR-DEGs with independent prognostic values, which were significantly associated with clinicopathological factors and immune checkpoint related genes. The risk prognostics model built on this basis had good predictive potential. In addition, targeted small molecule drugs, including calmidazolium and sulfasalazine, were predicted for mIR-DEGs. Further experimental results were consistent with the bioinformatics analysis. Conclusions: This study preliminarily confirmed that FGF17, PRKCG, SSTR1 and SCTR were targeted genes affecting renal cancer metastasis and related immune responses and can be used as potential therapeutic targets and prognostic biomarkers for renal cancer. Preliminary validation found that PRKCG and SSTR1 were consistent with predictions.